Safety and efficacy of Amplatzer duct occluder II and konar-MF™ VSD occluder in the closure of perimembranous ventricular septal defects in children weighing less than 10 kg - Yildiz, Kaan; Narin, Nazmi; Oksuz, Sedef; Ozdemir, Rahmi; Pamukcu, Ozge; Baykan, Ali; Ozyurt, Abdullah; Bagli, Sedat; Aktas, Rasit; Safak, Ikbal Nur; Atlan, Muhammed Akif; Bayam, Yunus Sezer; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction Device closure of perimembranous ventricular septal defects (pmVSD) is a successful off-label treatment alternative. We aim to report and compare the outcomes of pmVSD closure in children weighing less than 10 kg using Amplatzer Duct Occluder II (ADOII) and Konar-MF VSD Occluder (MFO) devices. Methods Retrospective clinical data review of 52 children with hemodynamically significant pmVSD, and sent for transcatheter closure using ADOII and MFO, between January 2018 and January 2023. Baseline, procedural, and follow-up data were compared according to the implanted device Results ADOII devices were implanted in 22 children with a median age of 11 months (IQR, 4.1–14.7) and weight of 7.4 kg (IQR, 2.7–9.7). MFO devices were implanted in 30 children with a median age of 11 months (IQR, 4.8–16.6) and weight of 8 kg (IQR, 4.1–9.6). ADOII were implanted (retrograde, 68.1%) in defects with a median left ventricular diameter of 4.6 mm (IQR, 3.8–5.7) and right ventricular diameter of 3.5 mm (IQR, 3.1–4.9) while MFO were implanted (antegrade, 63.3%) in defects with a median left ventricular diameter of 7 mm (IQR, 5.2–11.3) (p > 0.05) and right ventricular diameter of 5 mm (IQR, 2.0, 3.5–6.2) (p < 0.05). The procedural and fluoroscopy times were shorter with the MFO device (p < 0.05). On a median follow-up of 41.2 months (IQR, 19.7–49.3), valvular insufficiency was not observed. One 13-month-old child (6.3 kg) with ADOII developed a complete atrioventricular heart block (CAVB) six months postoperative and required pacemaker implantation. One 11-month-old child (5.9 kg) with MFO developed a CAVB 3 days postoperative and the device was removed. At 6 months post-procedure, only one child with MFO still experiences a minor residual shunt. There was one arterio-venous fistula that resolved spontaneously. Conclusion Both the MFO and ADOII are effective closure devices in appropriately selected pmVSDs. CAVB can occur with both devices. The MFO is inherently advantageous for defects larger than 6 mm and subaortic rims smaller than 3 mm. In the literature, our series represents the first study comparing the mid-term outcomes of MFO and ADOII devices in children weighing less than 10 kg.